The U. S. and the Philippines in our image, colonial days - Pearson, Andrew; Neudal, Eric.; Karnow, Stanley (Los Angeles, Calif. KCET, 1989)
Discusses the acceptance of American values in the Philippines throughout the years between the Spanish-American War and the Liberation from the Japanese. Mentions the growth of economic dependency and agrarian unrest.
Keywords: Philippines -- Politics and government; Philippines -- History